In vitro activities of antifungals alone and in combination with tigecycline against Candida albicans biofilms - Mayram Hacioglu (PeerJ, 2018)
Background Candida may form biofilms, which are thought to underlie the most recalcitrant infections. Methods In this study, activities of antifungal agents alone and in combination with tigecycline against planktonic cells and mature and developing biofilms of Candida albicans isolates were evaluated. Results Amphotericin B and echinocandins were found to be the most effective agents against mature biofilms, whereas the least effective agent was fluconazole. Furthermore, the most effective anti-fungal monotherapies against biofilm formation were amphotericin B and anidulafungin, and the least effective monotherapy was itraconazole. The combination of tigecycline and amphotericin B yielded synergistic effects, whereas combinations containing itraconazole yielded antagonist effects against planktonic cells. The combination of tigecycline and caspofungin exhibited maximum efficacy against mature biofilms, whereas combinations containing itraconazole exhibited minimal effects. Combinations of tigecycline with amphotericin B or anidulafungin were highly effective against C. albicans biofilm formation. Discussion In summary, tigecycline was highly active against C. albicans particularly when combined with amphotericin B and echinocandins.